2014
DOI: 10.1680/adcr.13.00050
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the cement process and cement clinker quality

Abstract: This paper presents a recently developed simulation model that can be used as a tool for evaluating sustainable development measures for cement and lime production processes. Examples of such measures are introducing new combustion technologies such as oxy-fuel combustion, using biomass fuel and using alternative materials in the raw material feed. One major issue when introducing process changes is the need to maintain product quality. In some ways, oxygen-enriched air combustion resembles oxy-fuel combustion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…ChemApp ™ also makes it possible to calculate solution phases not available in AspenPlus ™ . The predictive simulation tool has been validated for an operational lime plant and an operational cement plant . The system components are aluminum, carbon, calcium, chloride, iron, hydrogen, potassium, magnesium, nitrogen, sodium, oxygen, phosphorus, sulfur, silica, titanium, and zinc.…”
Section: Methodsmentioning
confidence: 99%
“…ChemApp ™ also makes it possible to calculate solution phases not available in AspenPlus ™ . The predictive simulation tool has been validated for an operational lime plant and an operational cement plant . The system components are aluminum, carbon, calcium, chloride, iron, hydrogen, potassium, magnesium, nitrogen, sodium, oxygen, phosphorus, sulfur, silica, titanium, and zinc.…”
Section: Methodsmentioning
confidence: 99%
“…Literature review of current uses of "bone ash or P2O5" in cement and concrete. 4,[14][15][16][17][18][19][20][21][22][23][24][25] with up to 10 wt% BA. Olutaiwo et al 29 investigated the replacement of cement with cow BA in rigid pavement construction, and concluded that a 20 wt% replacement rate of cement with BA was adequate for pavement construction, eventually leading to a cost reduction of around 10% when compared to a conventional concrete.…”
Section: Use Of Ba As a Cement Replacementmentioning
confidence: 99%
“…Many researchers have reported similar conclusions, 4,14–17 noting that the presence of phosphorous in the raw meal negatively impacts the PC clinker formation. Results included a lower amount of alite formed, incorporation of phosphorous into the alite and belite clinker phases (preferentially into the belite phase stabilizing it 18,19 ); and higher free lime content in the final clinker. This results in a cement exhibiting lower early strength (lower C 3 S content) and lower hydration heat development.…”
Section: Introductionmentioning
confidence: 99%
“…Cement is one of the important commodities for economic development. In terms of volume, concrete is the manmade material that is utilized the most [1]. Concrete is produced with cement.…”
Section: Introductionmentioning
confidence: 99%